Sharia Dress Code in Indonesia: The Dialectics of Islamic Law and Cultural Negotiation in Muslim Fashion - Hani Mustikasari; Rifqi Rifqi; Sumarta (Penerbit Hellow Pustaka, 2026)
This research aims to analyze the dynamics of Sharia clothing implementation within the context of the relationship between law and culture in Indonesia. The study employs a qualitative approach through a literature review of contemporary scientific sources from the 2020–2025 period. The focus of the study includes the interaction between Sharia normative provisions and social practices within the Indonesian Muslim fashion industry. The findings indicate that differing interpretations regarding the boundaries of awrah and Sharia standards have led to diverse clothing practices in society. Furthermore, a process of cultural negotiation occurs between universal Islamic values and local wisdom, giving birth to the distinct characteristics of Indonesian Muslim fashion. The Muslim fashion industry is also undergoing a transformation from a Sharia-compliance orientation toward a market-oriented approach, creating a dilemma between maintaining religious values and meeting economic demands. Additionally, digitalization and social media play a primary role in accelerating the transformation and reinterpretation of Sharia clothing, particularly among the younger generation. This research recommends the need for adaptive regulations, the development of credible Sharia certification standards, and an increase in public literacy to create a sustainable and contextual Muslim fashion ecosystem in Indonesia.